The energy heterologue: the EU-Russia energy dialogue, 2000-2012 - Talseth, L (2014)
The EU-Russia Energy Dialogue was launched in October 2000. Its goal was a binding energy agreement between Russia and the European Union, and possibly a wider political partnership. Today, however, the Energy Dialogue seems all but forgotten. How and why did the EU-Russia Energy Dialogue fail to define and create a legally binding energy partnership? There is scant literature about the Energy Dialogue. To the limited extent that the literature addresses the failure, it identifies either ideational, political, economic, geo- economic or institutional variables. But this separation is artificial. To bridge this divide I have developed a novel analytical framework using narratives and Bakhtin’s theory of dialogue. In this respect, the thesis is ideational or constructivist. However, unlike conventional constructivist accounts, which tend to downplay politics, this account emphasises power and conflict: Not dialogue as dual meaning, but many meanings, or ‘heterologue’. Narratives, as opposed to variables, are always in flux. To answer the how question: The dialogue failed because it could not forge a common narrative for the EU-Russia energy trade. Russia sought investment, whereas the EU wanted legal reform. Yet, the Energy Dialogue was a heterologue of conflicting narratives, both between and within Russia and the EU. I have coined six narrative clusters, used as Weberian ideal types: The ‘EUropean’, ‘EU15/25/27’, ‘Euro-Asian’, ‘Dual State’, ‘Statist’ and ‘Post-Imperial’ narratives. To answer the why question: Narratives unfold in time-space, and the initial misgivings were exacerbated by pre-existing narrative divergences (chapter 1), but also by subsequent political (chapter 2), business (chapter 3), geo-economic (chapter 4) and legal developments (chapter 5) – all influenced by the ebbs and flows of world oil prices. Thus, the failure of the Energy Dialogue was never pre-determined, or caused by a singular factor or event. It was shaped in the multidimensional, unfolding time-space of Russo-European relations.